PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR KECEPATAN DAN DEBIT DI KELAS V SDN 09 BELAKANG BALOK KOTA BUKITTINGGI - Insani, Mesi Yulia Sri; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This study aims to determine the effect of the problem based learning model of the results of speed and discharge in class V SD Negeri 09 Belakang Balok. This type of research is quantitative research with experimental methods and the design of Quasi Experiment. The sample technique uses a purposive sampling technique. The data analysis technique used is the t-test. The results of this study indicate that the average post-test experimental class is 83.33 and the average control class is 73.57. Analysis of the data from both classes obtained the results of tcount = 1.67 and ttable = 4.11 at a significant level of 0.05 so that tcount> ttable then ha is accepted. Thus it can be concluded that the Problem Based Learning model has a positive effect on the material speed and discharge in class V SD Negeri 09 Belakang Balok Bukittinggi.